Evaluation of the prevalence rate and risk factors associated with intrauterine growth retardation in Ilam province during 2014 - Raziyeh Mirzaei; Kourosh Sayehmiri; Mirhadi Mousavi; Ashraf Direkvand Moghadam; Khairollah Asadollahi (Mashhad University of Medical Sciences, 2017)
Introduction: Intrauterine growth retardation (IUGR) is a physiological and pathological process resulting in a slow fetal growth, and not only increases fetal mortality, but also is associated with adverse outcomes during infantile and adulthood. Therefore, this study was performed with aim to determine the prevalence and risk factors associated with IUGR in Ilam province. Methods: In this descriptive-analytical study, at first, the prevalence of IUGR was measured by cross-sectional method among all newborns during 2014 in Ilam province. Then, by designing a case-control study, 781 newborns (247 cases and 534 controls) were enrolled. All the newborns with birth weight below than 10th percentile were selected as case group and the newborns with birth weight above the 10th percentile were considered as control group. They were selected via simple randomization method. The required information including demographic and clinical data was obtained from hospital records. Data was analyzed by SPSS software (version 16) and Chi-square and Fisher exact tests and logistic regression model. P < 0.05 was considered significant. Results: The prevalence of IUGR among 9503 neonates in Ilam province during the study period was 2.8%. There was a significant relationship between IUGR and multiple pregnancy (P=0.0001), history of IUGR (P=0.02), mother's residency place (P=0.001), autoimmune diseases (P=0.03), kidney diseases (P=0.01), preeclampsia (P=0.0001), hyperemesis gravidarum (P=0.01), treated hypothyroidism (P=0.009) and mode of delivery (P=0.001). Conclusion: The prevalence of neonates born with IUGR in Ilam province was in accordance with global standards. Multiple pregnancy, history of IUGR, preeclampsia, hyperemesis gravidarum, autoimmune and kidney diseases and rural residency increase the chance of IUGR.